Implementasi Kebijakan Peraturan Daerah Kota Pangkalpinang Nomor 6 Tahun 2021 tentang Penataan dan Pembinaan Gudang - Ulpi Heriyanto; Andries Lionardo (Penerbit Goodwood, 2022)
Purpose: The purpose of this study is to discuss how and what factors influence the implementation of the Pangkalpinang City Regional Regulation No. 6 of 2021 concerning Warehouse Arrangement and Development. Method: The research method used in this study is a qualitative research method with a descriptive approach, with data collection techniques through interviews, observation and document review. Result: The results of the research show that the implementation of the Pangkalpinang City Regional Regulation policy No. 6 of 2021 concerning Warehouse Arrangement and Development has not been successful because it has not fulfilled all indicators. Seen from the aspect of communication it is not optimal, from the aspect of human resources and budget it is not optimal, in terms of the disposition aspect it is not optimal, and in terms of the bureaucratic structure aspect it is alredy optimal. Thus, it is still necessary to optimize the implementation of the Pangkalpinang City Regional Regulation Number 6 of 2021 concerning Warehouse Arrangement and Development